Risk factors for eating disorder psychopathology within the treatment seeking transgender population: the role of cross-sex hormone treatment - Jones, Bethany Alice; Haycraft, Emma; Bouman, Walter Pierre; Brewin, Nicola; Claes, Laurence; Arcelus, Jon (Wiley, 2018)
Many transgender people experience high levels of body dissatisfaction, which is one of numerous factors known to increase vulnerability to eating disorder symptoms in the cisgender (non-trans) population. Cross-sex hormones can alleviate body dissatisfaction so might also alleviate eating disorder symptoms. This study aimed to explore risk factors for eating disorder symptoms in transgender people and the role of cross-sex hormones. Individuals assessed at a national transgender health service were invited (N=563). Transgender people not on cross-sex hormones reported higher levels of eating disorder psychopathology than people who were. High body dissatisfaction, perfectionism, anxiety symptoms and low self-esteem were risk factors for eating psychopathology but, after controlling for these, significant differences in eating psychopathology between people who were and were not on cross-sex hormones disappeared. Cross-sex hormones may alleviate eating disorder psychopathology. Given the high prevalence of transgender identities, clinicians at eating disorder services should assess for gender identity issues.